Repeating earthquake swarms on Gede Volcano, West Java, Indonesia - Hidayat, Dannie (2022)
Over the past decade since the start of collaboration between Earth Observatory of Singapore (EOS) and Centre for Volcanology and Geohazard Mitigation (CVGHM), Gede Volcano has experienced frequent earthquake swarms, re ecting dynamic volcanic and tectonic processes. This volcano is located in the West Java Province 60-km from Indonesian capital Jakarta. We located the earthquake using seismic stations on Gede and Salak Volcanoes operated since 2011. We recorded earthquake swarms in 2012, 2015, 2016, 2019 and 2021 with hypocentres located under Gede Volcano and episode duration range from one day to a few weeks. We examine earthquakes from different earthquake swarm episodes where several tens of earthquakes are closely clustered in space and time. To further explore the evolution of the swarm, we carefully and consistently pick P and S wave arrivals owing to the highly repetitive and similar nature of waveforms and relocate these similar earthquakes. The hypocentres were clustered 1 km to the East of Gede active crater with depth range 2-3 km below the highest volcano topography. When we compared locations of different episodes, the swarms in 2012, 2019 and 2021 showed highly similar locations suggesting the nondestructed earthquake source. This could be magma pathway or a pre-existing fracture on the volcano. We hypothesize that the swarm was triggered by hydrothermal uid into a preexisting fault system, prompting release of accumulated stress. The ongoing work explore source mechanism of the earthquakes utilizing full wave inversion.